Rotating electrical machines of particular types or for particular applications Part 2. Specification for turbine-type - British Standards Institution (London BSI, 1988)
Rotating electric machines, Electric generators, Ratings, Rated power, Internal combustion engines, Vibration, Vibration control, Alternating-current generators, Direct-current generators, Name plates, Marking
Replaced By BS EN 60034-3:1996
Revised, Withdrawn
Cross References BS 2757, BS 4999:Part 101, BS 4999:Part 102, BS 4999:Part 104, BS 4999:Part 108, BS 5000:Part 99
Replaces BS 5000-2:1973
Keywords: Turbine-type synchronous machines -- Standards